AN ANALYSIS OF STUDENTS’ RESPONSES IN TEACHING ENGLISH LISTENING USING THE LINGOKIDS APPLICATION - Tia Nurhaifah; Sunara, Sunara; Ida Maulida (Journal of Innovation Research and Knowledge, 2026)
This research aims to investigate the utilization of Lingokids in teaching listening skills in English and investigate the reaction of learners throughout the learning process. The problem that is being studied is low motivation and lack of skills of listening comprehension due to traditional education methods on behalf of third-grade learners. A qualitative case study method was used in this research which involved ten third-grade students from SDN Setragalih in the academic year of 2025/2026. Data were collected through observations, interviews, and documentations with the help of Miles & Huberman interactive model. Results have proven that the application of Lingokids scored very good (95.8%). The utilization of audio-visual elements like music, games, and stories had helped students to develop their cognitive as well as affective engagement. Moreover, after four weeks of observation, there has been an increase in students' ability to comprehend directions, vocabulary development, and reactions to the sounds. Besides, positive emotions like interest and pleasure were noticed. Therefore, Lingokids can be seen as an effective digital educational application that provides engaging learning environment.